2010
DOI: 10.1080/10106049.2010.516843
|View full text |Cite
|
Sign up to set email alerts
|

Development of an inversion algorithm for dry snow density estimation and its application with ENVISAT-ASAR dual co-polarization data

Abstract: Radar remote sensing has great potential to determine the extent and properties of snow cover. Availability of space-borne sensor dual-polarization C-band data of environmental satellite-(ENVISAT-) advanced synthetic aperture radar (ASAR) can enhance the accuracy in measurement of snow physical parameters as compared with single polarization data measurement. This study shows the capability of Cband synthetic aperture radar (SAR) data for estimating dry snow density over snow covered rugged terrain in Himalaya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…The effect that backscattering from a smooth wet surface is much lower than from rough ground was used to detect wet snow and to predict melt water runoff [23]- [26]. Algorithms based on the polarimetric backscatter signal were developed and used for snow wetness and snow density determination [27], [28].…”
Section: Introductionmentioning
confidence: 99%
“…The effect that backscattering from a smooth wet surface is much lower than from rough ground was used to detect wet snow and to predict melt water runoff [23]- [26]. Algorithms based on the polarimetric backscatter signal were developed and used for snow wetness and snow density determination [27], [28].…”
Section: Introductionmentioning
confidence: 99%
“…Radar back scattering from a snow surface depends upon the dielectric constant of the 20 surface (Tiuri et al, 1984;Ulaby and Stiles, 1980;Rott, 1984), its roughness properties, and the geometry of the scattering (Evans, 1963;Ambach, 1980;Nyfors, 1982;Hallikainen et al, 1986;Matzler, 1987). Many mathematical models of surface scattering have been developed, some based on physical laws, some on empirical data fitting, and some on a combination of the two (Rees, 2006;Strozzi, 1996;Strozzi and 25 Matzler, 1998).…”
Section: Backscattering From Dry Snowpackmentioning
confidence: 99%
“…Furthermore, this study showed the possibility of inferring snow depths from combined parameters estimated with an L-band SAR image. Snehmani et al (2010) used C-band SAR data of ASAR-APS dual polarisation for snow density 15 estimation. In this approach for developing an algorithm for snow density estimation, the volume scattering model and the small perturbation model have been used with an exponential correlation (Ulaby et al, 1986) function for the surface backscattering contribution from the snow-ground interface.…”
Section: Sar For Snow Density Retrievalmentioning
confidence: 99%
See 2 more Smart Citations